Fermented Soy Products: Beneficial Potential in Neurodegenerative Diseases - Chan Ho Jang (Foods, 2021)
Fermented soybean products, such as cheonggukjang (Japanese natto), doenjang (soy paste), ganjang (soy sauce), and douchi, are widely consumed in East Asian countries and are major sources of bioactive compounds. The fermentation of cooked soybean with bacteria (Bacillus spp.) and fungi (Aspergillus spp. and Rhizopus spp.) produces a variety of novel compounds, most of which possess health benefits. This review is focused on the preventive and ameliorative potential of fermented soy foods and their components to manage neurodegenerative diseases, including Alzheimer’s and Parkinson’s diseases.